Faster topsoil organic matter transformation accompanies long-term carbon preservation in virgin Chernozems - Yurova, Alla Yu; Smirnova, M.A.; Kozlov, D.N.; Bardashev, D.R.; Lozbenev, N.I.; Stepanenko, V.M. (Geoderma Regional, 2025)
This study examines soil organic carbon (SOC) dynamics in different soil types across a micro-topographical gradient, focusing on topsoil SOC stabilization and turnover rates in virgin Chernozems. The thermodynamic origin of differences in SOC decomposability (henceforth referred to as “quality”, or “q”) between soil types is explained using a Q model that treats quality as a continuous variable rather than assuming the presence of discrete SOC pools. The model's calibration is focused on enabling effective assessment of overall SOC stocks in the topsoil (the topmost 10 cm) and the total carbon stock in the uppermost 50 cm while using radiocarbon turnover rates as secondary constraints that may be needed due to limited data availability. The SOC turnover time in the topsoil determined by modeling the SOC quality distribution function was shown to agree well with empirical findings from similar study sites, indicating that SOC turnover times are around 6–10 years in surface layers but millennia in deeper layers. This reinforces the importance of distinguishing between topsoil and subsoil carbon stocks and their respective stabilization mechanisms in Chernozems. The analysis also highlights the influence of soil temperature and moisture conditions on soil organic carbon (SOC) dynamics: high topsoil moisture levels due to lateral water inputs increase SOC stabilization and thus reduce q, so wetter sites have enhanced carbon stocks. This outcome aligns with existing theories of humification in which water availability emerges as a crucial factor influencing SOC preservation and stabilization. Wetter soils also exhibit reduced decomposition due to lower temperature. This interplay between moisture, temperature, and microbial respiration rates necessitates a reevaluation of conventional beliefs about the behavior of SOC in different water regimes that stress the impact of moisture on soil respiration but not SOC stabilization. These findings also highlight the need to account for microtopographic variation, especially in semi-arid regions, in soil management programs seeking to optimize SOC retention and overall soil health. The insights into SOC dynamics presented here will be valuable for improving soil management strategies to enhance carbon sequestration in various soil types under changing climatic conditions.